Impact of Reading Newspaper on the Development of Second Language Learners’ writing Skills - Fathima Suzani Mohamed Salih; Mohamed Jabeer Fathima Sujani; MR. Rishad Muhammed (Elementaria: Journal of Educational Research, 2024)
This research investigates challenges in English writing skills among Grade 9 online learning students in the Kalmunai Zonal Education area of Sri Lanka. The objectives of the study are; to examine how reading newspaper helps in learners in enhancing vocabulary, to identify the effectiveness of reading newspaper on the development of grammar competency, to assess the usefulness of newspaper reading on the development of accuracy in writing, to analyze the effectiveness of newspaper reading on the development of reading comprehension. Employing questionnaires for quantitative data collection, the study reveals a substantial consensus (98%) favoring the positive influence of newspapers on writing skills. Participants predominantly express strong agreement in relation to enhanced English writing skills, improved vocabulary, and better articulation of ideas through newspaper reading. Minimal disagreement responses underscore a consensus in recognizing the positive impact on language proficiency. Qualitative insights from focus group interviews complement quantitative data, offering depth to statistical trends. Participants articulate nuanced experiences, highlighting newspapers’ positive effects on writing skills, creativity, critical thinking, and reading comprehension. These narratives enrich understanding of how and why newspaper reading contributes to language skill enhancement, particularly in writing. The synthesis of quantitative and qualitative findings provides a comprehensive perspective, affirming multifaceted benefits of regular newspaper engagement. Beyond quantifying prevalent positive attitudes, the research delves into participants’ perceptions, motivations, and varied experiences. The study’s quantitative data is derived from questionnaires, while qualitative insights are gathered through focus group interviews, establishing a methodologically robust foundation for exploring the intricate relationship between newspaper reading habits and language skills among second language learners. The research reveals that newspapers emerge as valuable educational tools, fostering language development across dimensions and serving as tools to enhance writing skills among Grade 9 online students.